The growth analysis of soybean cultivars on the application of banana pseudo-stem bokashi in Samas Coastal Land, Yogyakarta - Khavid Faozi; Prapto Yudono; Didik Indradewa; Azwar Ma'as (Jurnal Ilmu Pertanian, 2021)
A coastal sandy land is a potential land used for soybean cultivation. The success in developing soybeans in coastal sandy land depends on the suitability of cultivars used and the cultivation technology applied. Therefore, this study aimed to analyze the growth of twelve soybean cultivars in coastal sandy land as affected by the application of banana pseudo-stem bokashi. The experiment was carried out in factorial randomized complete block design with three replications. The treatment factors consisted of rates of bokashi (0, 20, 40, and 60 ton.ha-1) and 12 soybean cultivars (Anjasmoro, Argomulyo, Burangrang, Demas 1, Dena 1, Devon 1, Gamasugen 1, Gema, Gepak Ijo, Grobogan, Kaba, and Slamet). The net assimilation rate, relative growth rate, and root and shoot dry weight were affected by the bokashi rates, with varying responses according to the soybean cultivar. Demas 1 cultivar was the most adaptive cultivar in coastal sandy land based on its ability to accumulate dry matter of plants. The accumulation of dry matter of roots and shoots increased with bokashi application and the optimum rate were 42.83 ton.ha-1 and 45.56 ton.ha-1, respectively.